2023
DOI: 10.3390/nano13182570
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Photocurrent Microscopy in Single Crystal Multidimensional Hybrid Lead Bromide Perovskites

Elena Segura-Sanchis,
Rocío García-Aboal,
Roberto Fenollosa
et al.

Abstract: We investigated solution-grown single crystals of multidimensional 2D–3D hybrid lead bromide perovskites using spatially resolved photocurrent and photoluminescence. Scanning photocurrent microscopy (SPCM) measurements where the electrodes consisted of a dip probe contact and a back contact. The crystals revealed significant differences between 3D and multidimensional 2D–3D perovskites under biased detection, not only in terms of photocarrier decay length values but also in the spatial dynamics across the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The photocurrent maps indicated that the effective decay length cuts near the border, indicating the importance of border recombination centres in monocrystalline samples [36]. The multidimensional 2D-3D perovskites showed a single exponential fitting model, while the 3D perovskites confirmed a fast and slow charge carrier migration dynamic inside the crystal [36].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The photocurrent maps indicated that the effective decay length cuts near the border, indicating the importance of border recombination centres in monocrystalline samples [36]. The multidimensional 2D-3D perovskites showed a single exponential fitting model, while the 3D perovskites confirmed a fast and slow charge carrier migration dynamic inside the crystal [36].…”
Section: Introductionmentioning
confidence: 94%
“…The study by Segura-Sanchis et al [ 36 ] focused on scanning photocurrent microscopy (SEM) in single-crystal multidimensional hybrid lead bromide perovskites. Their composition played an important role in their optoelectronic properties, mainly the effect on the photogenerated transport charges along the microcrystals [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations